Breaking up the play: The relationship between legal stops and winning in team handball - Laxdal, A.; Ivarsson, A. (International Journal of Sports Science & Coaching, 2023)
The purpose of this study was to examine the relationship between legal stops and winning in team handball. Real-time analysis was performed on all games played in the Icelandic elite division for both males and females (regular season and playoffs) between 2017-2021 (854 games [570 male games, 284 female games], 32,392 legal stops in total). Legal stops were assessed as any physical action by a defensive player that resulted in the stop of play, without the defensive player being penalized or the offensive player receiving a 7-meter throw. The results from a multinomial logistic regression analysis indicated that legal stops were significantly associated with winning games in the male league. No statistically significant relationship was found between illegal stops and game outcome for either sex. However, 2-minute suspensions were found to be positively associated with winning in the male league.